Feedback practices as part of signature pedagogy for clinical placements. Issue 2 (4th March 2021) - Penman, Merrolee; Tai, Joanna; Thompson, Tanya; Thomson, Kate
ABSTRACT: Signature pedagogies have been identified for medicine and nursing, however are not yet resolved for allied health. This paper explores feedback as part of the signature pedagogy for health professions clinical placements. It adopts a Theory of Practice Architectures perspective to understand feedback practices, within the context of placements which involved student mentoring. Two dominant practices were found to characterise feedback: creating a comfortable learning environment through feedback, and achieving feedback for learning. Analysis of the arrangements revealed the impact of educators' caseloads in enabling, and more often, constraining feedback practices. Student mentors ensured that feedback occurred, suggesting that students can recognise and contribute to feedback as part of a signature pedagogy. Further, similarity across the two professions in this study supports the contention that there is a common signature pedagogy for clinical placements. This has implications for educator development and the role of students within workplace learning.